UJI VALIDITAS DAN RELIABILITAS KUESIONER KEPATUHAN MGLS (MORISKY, GREEN, LEVINE ADHERENCE SCALE) VERSI BAHASA INDONESIA TERHADAP PASIEN EPILEPSI - Iin Ernawati; Wardah Rahmatul Islamiyah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
Epilepsy is a chronic brain disease that is characterized by seizures spontaneously, recurs and there is no improvement in each seizure. One measure of therapy epilepsy is decreased or loss of seizures. One of the things that still causes the uncontrolled seizure is adherence. Measurement of adherence in epilepsy patients is one of the tool for know related to the type of therapy and intervention provided. One of the adherence questionnaires that can be used is MGLS (Morisky, Green, Levine Scale Adherence Scale). The MGLS questionnaire is a adherence questionnaire with 4 items of questions, where the questionnaire questions can describe the level of patient adherence in drug consumption. The purpose of this study is to test the validity and reliability of the MGLS questionnaire with the intention that the questionnaire can be applied to patients.This study was a descriptive observational study conducted on epilepsy patients at Airlangga University Hospital. Sampling was done through consecutive sampling method, obtained 42 epilepsy patients between May-July 2018. Validity test was carried out using the Pearson correlation method (correction value ≥0.3) and the reliability test using internal cronbach alpha coefficient ≥0.6. Based on the results of the validity test it is known that the correlation score of each question with the total score is known to correlate more than r table (N = 42) 0.3496. These results indicate that all questions on the Indonesian version of the MGLS questionnaire are valid. Reliability test showed cronbach alpha coefficient 0.634> 0.6 (p <0.05). The conclusion of this study is the valid and reliable MGLS Indonesian version of the questionnaire instrument to determine the level of adherence in epilepsy patients.